2017
DOI: 10.1155/2017/4268962
|View full text |Cite
|
Sign up to set email alerts
|

ACE Inhibitor-Induced Angioedema following Cervical Spine Surgery

Abstract: Angioedema is a well-known side effect of angiotensin converting enzyme inhibitors (ACEi). However, ACE inhibitors induced angioedema after cervical surgery is a rare condition. They result in increased levels of circulating bradykinins. Rare cases of angioedema following local trauma in patients using ACE inhibitors have been published. We present such a case. A 54-year-old Caucasian female with a history significant for hypertension, controlled with lisinopril, was admitted for routine cervical spine surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The available literature contains many case reports of angioedema in surgical patients, suggesting direct injury caused by perioperative trauma (eg, intubation, lumbosacral spine surgery, c-spine surgery, shoulder surgery) as a trigger for angioedema in patients taking ACEIs or angiotensin II receptor blockers [ 3 , 7 , 14 , 15 ]. However, our search in PubMed (March 10, 2023) yielded only 1 case of local trauma-related angioedema outside the perioperative period, in a patient who bit her upper lip [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available literature contains many case reports of angioedema in surgical patients, suggesting direct injury caused by perioperative trauma (eg, intubation, lumbosacral spine surgery, c-spine surgery, shoulder surgery) as a trigger for angioedema in patients taking ACEIs or angiotensin II receptor blockers [ 3 , 7 , 14 , 15 ]. However, our search in PubMed (March 10, 2023) yielded only 1 case of local trauma-related angioedema outside the perioperative period, in a patient who bit her upper lip [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…While angioedema as a potentially life-threatening adverse reaction of angiotensin-converting enzyme inhibitors (ACEIs) is well-recognized, angioedema as an adverse reaction of angiotensin receptor blockers (ARBs) is relatively less studied and less reported [ 1 , 6 ]. Indeed, many cases of spontaneous angioedema and perioperative angioedema in patients taking ACEIs have been reported [ 7 ]. However, angioedema following local trauma in patients taking ARBs is rare in the literature, and our literature review in PubMed revealed only 1 similar case [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Angioedema is one of the earliest causes of postoperative airway compromise after ACSS and typically presents within 6–12 h. However, due to its rarity, it is often misdiagnosed [ Table 2 ]. [ 4 , 8 ] Further, angioedema is one of the known side effects of both risedronate and parecoxib, and has also been associated with a history of smoking; notably, our patient was a smoker [ Table 2 ]. [ 1 - 4 , 8 ] It is well known that corticosteroids reduce the risk of reintubation following ACSS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 8 ] Further, angioedema is one of the known side effects of both risedronate and parecoxib, and has also been associated with a history of smoking; notably, our patient was a smoker [ Table 2 ]. [ 1 - 4 , 8 ] It is well known that corticosteroids reduce the risk of reintubation following ACSS. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Few cases of angioedema following anesthesia in patients using ACE inhibitors have been reported. [ 4 7 ]. However to the best of our knowledge, none has reported intraoperative angiotensin II receptor blocker-induced angioedema.…”
Section: Introductionmentioning
confidence: 99%